2020
DOI: 10.5194/essd-2020-139
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Petrophysical and mechanical rock property database of the Los Humeros and Acoculco geothermal fields (Mexico)

Abstract: Abstract. Petrophysical and mechanical rock properties are key parameters for the characterization of the deep subsurface in different disciplines such as geothermal heat extraction, petroleum reservoir engineering or mining. They are commonly used for the interpretation of geophysical data and the parameterization of numerical models and thus are the basis for economic reservoir assessment. However, detailed information regarding petrophysical and mechanical rock properties for each relevant target horizon ar… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Bakker et al 2019;Parisio et al 2019Parisio et al , 2020. The strength and mechanical properties of volcanic rocks are also of important in the context of geothermal energy exploitation (Siratovich et al 2016;Eggertsson et al 2020;Weaver et al 2020;Heap et al 2020c;Weydt et al 2020). Finally, the failure mode of volcanic rocks also controls how their physical properties evolve.…”
Section: Introductionmentioning
confidence: 99%
“…Bakker et al 2019;Parisio et al 2019Parisio et al , 2020. The strength and mechanical properties of volcanic rocks are also of important in the context of geothermal energy exploitation (Siratovich et al 2016;Eggertsson et al 2020;Weaver et al 2020;Heap et al 2020c;Weydt et al 2020). Finally, the failure mode of volcanic rocks also controls how their physical properties evolve.…”
Section: Introductionmentioning
confidence: 99%
“…Various geological (Ferriz and Mahood 1984;Carrasco-Núñez et al 2017a, b), geochemical (Prol-Ledesma and Browne 1989;Martıńez-Serrano 1993Izquíerdo et al 2011Izquíerdo et al , 2015, geophysical (Lermo et al 2008;Arzate et al 2018), and hydrological studies (Tello 2005) have been performed in the past and most recently within the framework of the GEMex project (EU-H2020, GA Nr. 727,550;Jolie et al 2018;Weydt et al 2018Weydt et al , 2021bLucci et al 2020;Urbani et al 2020Urbani et al , 2021 to improve reservoir understanding and to create conceptual (Cedillo 2000;) and 3D geological models (Calcagno et al 2020;Deb et al 2019). However, even after more than 40 years of exploration, information on rock properties of the different geological units in the study area were scarce or not available.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies have provided values for the thermal properties of volcanic rocks for modelling (Horai et al, 1970;Fujii and Osako, 1973;Robertson and Peck, 1974;Bagdassarov and Dingwell, 1994;Whittington et al, 2009;Romine et al, 2012;Mielke et al, 2015Mielke et al, , 2016Mielke et al, , 2017Vélez et al, 2018;Heap et al, 2020;Weydt et al, 2021;Heap et al, 2022a). These studies, and others, have shown that porosity plays a first-order role in dictating thermal properties of volcanic rocks.…”
Section: Introductionmentioning
confidence: 99%